(untitled) (Applied Biological Research, 2017)
The present study was aimed to characterize the early generation sugarcane (Saccharum officinarum) clones. Thirty-four sugarcane genotypes from different cross combinations representing six bi parental crosses, twenty-four general crosses, three poly-crosses and one-selfed were planted along with two checks. A total of 20 SSR markers were used to assess the gen etic diversity of which 93.5% were polymorphic. Polymorphic information content was used to determine allele diversity at each locus ranged from 0.141 (SOMS118) to 0.314 (UGSM585). The average expected gene diversity ranged from 0.105 (SOMS120) to 0.396 (UGSM-585). Genetic similarity based by Jaccard’s similarity coefficient ranged from 0.419 to 0.96. Dendrogram constructed using UPGMA cluster analysis revealed two distinct groups among S. officinarum species clones and two commercial checks and ordered the populations of 36 genotypes into five clusters with varying number of members proved SSR marker to be an effective tool for assessing genetic diversity among sugarcane clones.